2015
DOI: 10.4187/respcare.04341
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Control Assessment Tools

Abstract: , and they emphasize periodic assessment of asthma control once treatment is established. Accurate assessment of asthma control is difficult due to the complexity of asthma control and due to the limitations in the traditional methods of assessment, such as lung function tests, physician assessment, and patients' self-assessment. Relying solely on the role of lung function tests is insufficient to reflect the status of asthma control, since patients with asthma may have normal spirometry between exacerbations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 75 publications
0
20
0
Order By: Relevance
“…Although some asthma control assessment tools that are validated or adapted for use in children assess the child's perception of their own asthma control (cACT for those <12 years and the ACT for those ≥12 years), only two ascertain the caregiver's perception of the child's asthma control (adapted ATAQ and Lara Asthma Symptom Score, or LASS). 12 ATAQ, which was developed for, and validated in, adults, has been adapted and validated for use in children and includes the following question, which is asked of caregivers: "Do you believe that your child's asthma was well controlled in the past 4 weeks?" 13 Though the ATAQ is one of two tools that captures caregiver perception of the child's control, it has not been validated in low-income, minority populations.…”
Section: Discussionmentioning
confidence: 99%
“…Although some asthma control assessment tools that are validated or adapted for use in children assess the child's perception of their own asthma control (cACT for those <12 years and the ACT for those ≥12 years), only two ascertain the caregiver's perception of the child's asthma control (adapted ATAQ and Lara Asthma Symptom Score, or LASS). 12 ATAQ, which was developed for, and validated in, adults, has been adapted and validated for use in children and includes the following question, which is asked of caregivers: "Do you believe that your child's asthma was well controlled in the past 4 weeks?" 13 Though the ATAQ is one of two tools that captures caregiver perception of the child's control, it has not been validated in low-income, minority populations.…”
Section: Discussionmentioning
confidence: 99%
“…Several instruments have been developed for measuring asthma control. In their review, Alzahrami and Becker [1] identified: the Asthma Control Test (ACT), the Asthma Control Questionnaire (ACQ), the Asthma Therapy Assessment Questionnaire (ATAQ), the Lara Asthma Symptom Scale (LASS) and the Childhood Asthma Control Ttest (CACT). The authors also identify a number of limitations for each tool.…”
Section: Discussionmentioning
confidence: 99%
“…A narrower search for reviews of asthma control assessment tools in pediatric care (using the terms “asthma control” and “assessment” and “pediatric” and “review”) yielded 32 results. While these articles addressed multiple aspects of pediatric asthma symptom control across various settings of care and geographic regions, one recently published article, sought to provide a comprehensive review of asthma control assessment tools for both adult and pediatric asthma, making it highly relevant to this integrative review [42]. Section 3.3 discusses key gleanings from the selected article.…”
Section: Methodology For the Integrative Reviewmentioning
confidence: 99%
“…Asthma symptom control (stream #3c). As discussed in Section 2.5, the review process for measures of pediatric asthma symptom control identified a recently published comprehensive article on asthma control assessment tools [42]. This review examined tools that have been validated, found to have established psychometric properties, and have been extensively studied in terms of their ability to reflect the overall status of asthma control.…”
Section: Key Findings From the Integrative Reviewmentioning
confidence: 99%